2014
DOI: 10.1186/cc13341
|View full text |Cite
|
Sign up to set email alerts
|

Use of pulse pressure variation and stroke volume variation in spontaneously breathing patients to assess dynamic arterial elastance and to predict arterial pressure response to fluid administration

Abstract: Introduction We aimed to audit the prescribing practice on a busy 14-bedd general ICU, and develop standardised practices and tools to improve safety. Prescribing errors occur as commonly as in 10% of UK hospital admissions, costing 8.5 extra bed days per admission, and costing the National Health Service an estimated £1 billion per annum [1]. The majority of these mistakes are avoidable [2]. Methods We audited the daily infusion charts of all patients in three separate spot checks, over 1 week. We assessed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…First, hemodynamic parameters were assessed by non-invasive pulse contour analysis (ClearSight System ® ). However, this technique has extensively been validated against invasive hemodynamic measurements and is an established method in clinical practice [14,26,27]. Second, we did not measure other hemodynamic parameters such as pulse pressure, central arterial blood pressure, markers of arterial stiffness that have been shown to be affected by empagliflozin treatment for 6 weeks [28].…”
Section: Discussionmentioning
confidence: 99%
“…First, hemodynamic parameters were assessed by non-invasive pulse contour analysis (ClearSight System ® ). However, this technique has extensively been validated against invasive hemodynamic measurements and is an established method in clinical practice [14,26,27]. Second, we did not measure other hemodynamic parameters such as pulse pressure, central arterial blood pressure, markers of arterial stiffness that have been shown to be affected by empagliflozin treatment for 6 weeks [28].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the non-invasive Nexfin monitor for haemodynamic measurements. It measures continuous arterial blood pressure and subsequently calculates CO [5,13,[16][17][18][19][20][21][22] and PPV [5,11,13,23,24] from the arterial pressure waveform. It is restricted to patients with normal peripheral perfusion, and several studies have reported on its limited value in critically ill patients or during septic shock [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Cecconi and colleagues, it was shown that PPV and SVV with the Nexfin can be used to predict fluid responsiveness in spontaneously breathing patients who are not subjected to forced inspiration or controlled breathing manoeuvres [13]. They assumed that spontaneous breathing artefacts affect the PPV and SVV equally, and this would therefore have no effect on the PPV/SVV ratio reflecting dynamic arterial elastance [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations